Hierarchical Control with Guaranteed Fault Diagnosability. Issue 24 (2018) - Stoican, Florin; Petzke, Felix; Prodan, Ionela; Streif, Stefan
Abstract: A multiple time-scale hierarchical control approach with guarantees for active fault diagnosability (detection and isolation) is presented. Robust positive invariance notions are used to provide a set-membership test for FDI validation at the low level and sufficient constraints for guaranteeing FDI at the high level. Due to the computational burden of the involved bilinear optimization problem, the high-level reference governor operates at a slower sampling time than the controller of the low-level system. Therefore, corner cutting avoidance constraints are imposed such that the faster-sampled lower level is still guaranteed to function properly. A case study illustrates the presented theoretical notions.